Introduction to the Ethics of Emerging Technologies - Reijers, Wessel; Thomas Young, Mark; Coeckelbergh, Mark

Das Gesicht des Weltalls anschauen. Rilkes Ägypten-Reise und der Kulturtourismus - Schulte Eickholt, Swen (diMaG)
Als Rilke im Frühjahr 1911 eine zuvor begonnene Afrika-Reise mit einem Nildampfer von Thomas Cook in Ägypten fortsetzt, wird ihm schnell klar, dass das Tempo des Massentourismus in Konflikt mit seinen Sehbedürfnissen kommt. Der touristische Blick entsteht in zeitlicher und gedanklicher Nähe zum Kolonialismus und führt eine Form eurozentrisch-hegemonialer Weltbeherrschung vor ‒ wobei der Tourist als Typus auch im Inland schon im 19. Jahrhundert dem Reisenden als Negativfigur entgegengestellt wird. Entgegen gegenwärtiger Werbestrategien ist auch der Kulturtourismus von seinen Anfängen her nicht frei von Elementen des Massentourismus und eines die Fremde beherrschenden Blicks. Dass eine immer schon vorgeprägte Erwartungshaltung die erwartete Erschütterung erschwert, wird Rilke auf seiner Reise deutlich, die er nicht zuletzt durch die Ägypten-Reise seiner Frau vorbereitet hat. So versucht er den Ambivalenzen des industrialisierten Kulturtourismus zu entkommen und empfindet am Ende doch nur die strukturelle Untragbarkeit der touristischen Situation, die schon vor der Reise durch die Hoffnung auf authentisches Erleben hoffnungslos kontaminiert ist.

How to Govern the Confidence Machine? - de Filippi, Primavera; Mannan, Morshed; Reijers, Wessel (Regulation & Governance)
ABSTRACT Emerging technologies pose many new challenges for regulation and governance on a global scale. With the advent of distributed communication networks like the Internet and decentralized ledger technologies like blockchain, new platforms emerged, disrupting existing power dynamics and bringing about new claims of sovereignty from the private sector. This special issue addresses a gap in the literature by focusing the discourse on the issue of trust and confidence in the digital realm. In particular, looking at the evolution of the web (from Web 1.0, to Web 2.0, and then Web 3), this article analyses how every iteration reflects a different way of dealing with the problem of trust online, resulting in a different regulation and governance landscape. Technology is often regarded as a new lever of regulation, attempting to resolve the problem of “trust” online, either through the introduction of a new trusted authority (Web 2.0) or through the introduction of technological guarantees that provide more assurance—or “confidence”—in the way interactions can be operationalized (Web 3). Yet, each of these technologies also introduce new risks and governance costs, ultimately shifting the problem of trust in a new direction rather than resolving it or removing the need for trust altogether. The main contribution of the articles in this special issue is providing a better understanding of the trust challenges faced and posed by emerging technologies and demonstrating how they affect institutional governance—in both theory and practice—with a view to help policymakers find appropriate answers to these challenges.

Erfolgreich Studieren - sinnvolle Lernstrategien erlernen (Posterbeitrag) - Nölle, Florian; Schmid, Hans-Joachim; Bentrup, Leon Alexander; Temmen, Katrin (MINT-Symposium)

Le théâtre au service de la formation des enseignants – Entwicklung eines theaterpädagogischen Lehrkonzepts für die Förderung der performativen Lehrkompetenz angehender Fremdsprachenlehrkräfte - del Valle, Victoria (TIPA. Travaux interdisciplinaires sur la parole et le langage)
Im Fremdsprachenunterricht haben theaterpädagogische Methoden eine lange Tradition und werden mittlerweile als Prinzipien einer performativen Didaktik angeführt (vgl. Bryant & Zepter, 2022; Hensel, 2020; Sambanis & Walter, 2021; Schewe, 2020; Sting, 2023). In Anlehnung an diesen Diskurs wird im vorliegenden Artikel der Begriff théâtre appliqué (vgl. Martinez Thomas, 2017) verwendet, um die theaterpädagogischen Wurzeln der performativen Fremdsprachendidaktik zu betonen. Der Artikel skizziert des Weiteren ein Projekt, das einen Rahmen für die Integration theaterbasierter Methoden in die universitäre Lehrkräftebildung in Deutschland schafft. Ziel ist es, die performative Lehrkompetenz angehender Fremdsprachenlehrkräfte zu fördern und den Körper als einen zentralen Mitgestalter des Sprachenunterrichts hervorzuheben. Dabei verschiebt sich der Fokus von der Frage, warum Theaterpädagogik für das Sprachenlernen förderlich ist, hin zu der Frage, wie Theatermethoden in der universitären Lehrkräfteausbildung eingesetzt werden können.Zu diesem Zweck wird die Entwicklung eines Lehrkonzepts für die universitäre Lehrerausbildung in den Fächern Französisch und Spanisch in Nordrhein-Westfalen (Master of Education) vorgestellt. Diese Entwicklung gliedert sich in drei Zyklen, die auf Design-Based Research basieren (vgl. Dube & Prediger, 2017): Zyklus 1 - Konzeptentwicklung, Zyklus 2 - Pilotierung und Überarbeitung basierend auf rekonstruktivem Feedback und Zyklus 3 - Evaluation des Gesamtkonzepts und Datenanalyse zu den Wahrnehmungen der Studierenden. Da der dritte Zyklus noch nicht abgeschlossen ist, werden erste Beobachtungen und die erwarteten Ergebnisse in Aussicht gestellt.

Implementing a computational cognitive process model of medical diagnostic reasoning - Battefeld, Dominik; Kopp, Stefan (Proceedings of KogWis 2025: Conference of the German Cognitive Science Society)

A Computational Approach to Adaptive Explanation Generation Based on Cognitive Partner Models - Robrecht, Amelie; Kopp, Stefan (Proceedings of the KogWis 2025)

Manners Matter: Action history guides attention and repair choices during interaction - Singh, Amit; Rohlfing, Katharina J. (IEEE International Conference on Development and Learning (ICDL))
This study investigated how action histories – unfolding sequences of actions with objects – provide a context for both attentional allocation and linguistic repair strategies. Building on theories of enactive cognition and sensorimotor contingency theory, we experimentally manipulated action sequences (action history) to create either simple or rich “situational models,” and investigated how these models interact with attention and reflect in linguistic processes during human–robot interaction. Participants (N = 30) engaged in a controlled object placement task with a humanoid robot, where the action (manner) information was either provided or omitted. The omission elicited repair behaviors in participants that were in focus of our investigation. For rich models (competing action possibilities) participants demonstrated: a) increased attentional reorientation, reflecting active engagement with the situational model b) preference for restricted repairs, targeting the specific source of trouble in action selection. Conversely, a simple situational model led to more generalized attention patterns and open repair strategies, suggesting weaker constraints on internal processing. These findings highlight how situational structures emerge externally to scaffold internal cognitive processes, with action histories serving as a crucial context for the interface between perception, action, and language. We discuss how to implement such a tight loop in the assistance of a system.
Keywords: Attention; Action; Repairs; Task model; HRI; Eyemovement

MUNDEX Annotations - Buschmeier, Hendrik; Grimminger, Angela; Wagner, Petra; Lazarov, Stefan Teodorov; Türk, Olcay; Wang, Yu

TRR 318, Project A01, WP 2.1. Scales manual - Buhl, Heike M.; Herrmann, Paula; Bolinger, Dean X.

TRR 318, Project A01, WP 2.2. Scales manual - Buhl, Heike M.; Herrmann, Paula; Bolinger, Dean X.

Embedding Psycholinguistics: An Interactive Framework for Studying Language in Action - Singh, Amit; Rohlfing, Katharina J. (6th Biannual Conference of the German Society for Cognitive Science, Bochum, Germany)
We introduce a method to study online language processes in human--robot interactive setup. In this interaction, language mediated eye movements can be studied as the dialogue unfolds between human and a robot. Traditionally, real-time linguistic processes are studied using visual world paradigms (VWP), where either the comprehension or the production tasks are implemented on screens for controlled investigations. Going beyond these traditional and unidirectional approach, we bring together production--comprehension loop with the help of a humanoid robot to preserve interactivity in an ecologically valid yet controlled setup. We discuss the potential of such setups for designing and evaluating findings from language--vision interplay in psycholinguistics. Our setup shows a potential to depart from traditional screen based experiments, balancing the dynamics of the interaction with control of the human behaviors.

Die Perspektive von Berufseinsteiger*innen: Die Bedeutung des Praxissemesters für den eigenen Professionalisierungsprozess. - Bloh, Bea; Homt, Martina; Wehde, Janis

Linking ion formation to fuel conversion in laminar flames of a potential surrogate fuel - Keksel, Ewald; Kruse, Simon; Gonchikzhapov, Munko; Kasper, Tina

Determination of flame temperatures using thermocouples in transient measurements (Poster) - Wortmeier, Andreas; Gonchikzhapov, Munko; Kasper, Tina

Diskussionspunkte, offene Fragen - Süßmann, Johannes (Das Heilige (in) der Kultur. Unverfügbarkeit – Latenz – Widmung)
Keywords: Heilig; Heiligkeit; Heiligenverehrung; Kulturtheorie; Forschungsfragen; Modellbildung; Begriffsbildung; Übersetzen; Kulturalität; Universalität; Postkolonialismus; Medialität; Bildlichkeit; Schriftlichkeit; Paragone

Development and Implementation of Diversity Programs in Large Collaborative Research Projects: An Example From Germany - Lorke, Mariya; Amelung, Rena; Kuchling, Peter; Paaßen, Benjamin; Pein-Hackelbusch, Miriam; Schloots, Franziska Margarete; Schulz, Klara; Nauerth, Annette (Diversity & Inclusion Research)
ABSTRACT In recent years, there has been an increasing awareness of the importance of incorporating diversity into research projects, focusing on both how they are conducted and their content. Funding organizations have started to require that research applicants pay attention to inclusion and diversity by considering gender dimensions and other diversity factors in their project plans and ensuring gender equality during execution. Based on an extensive literature research and expert discussions on how to develop and implement diversity strategies in large collaborative research projects, we argue that there is a lack of practical advice in existing literature. Drawing from our own experiences in conceptualizing and implementing a Diversity Program across four universities in Germany, we propose a framework for effectively integrating diversity into collaborative research initiatives across various academic fields.
Keywords: collaborative research projects; diversity strategy; gender equality

Das Heilige (in) der Kultur. Unverfügbarkeit – Latenz – Widmung
Keywords: Heilig; Heiligkeit; Heiligenverehrung; Kulturtheorie; Christentum; Judentum; Religion; Anthropologie

Zwischen Erfahrung und Evidenz? – Eine Analyse der Quellennutzung von Lehrkräften im Berufseinstieg - Homt, Martina; Bloh, Bea; Wehde, Janis

Auf dem Weg zum Historiker. Darstellungsexperimente in Leopold Rankes Erstlingswerk ›Geschichten der romanischen und germanischen Völker von 1494 bis 1535‹ - Süßmann, Johannes (Leopold Rankes Frankfurter Jahre)
Keywords: Ranke; Leopold; Frankfurt/Oder; Geschichtsdarstellung; Romantik; Geschichtstheorie; Erkenntniskritik; Anschauung